Decreased bone mineral density in experimental myasthenia gravis in C57BL/6 mice - Minako Oshima; Akiko Iida-Klein; Takahiro Maruta; Philip R. Deitiker; M. Zouhair Atassi (Taylor & Francis Group, 2017)
Experimental autoimmune myasthenia gravis (EAMG), an animal model of myasthenia gravis (MG), can be induced in C57BL/6 (B6, H-2 b) mice by 2−3 injections with Torpedo californica AChR (tAChR) in complete Freund's adjuvant. Some EAMG mice exhibit weight loss with muscle weakness. The loss in body weight, which is closely associated with bone structure, is particularly evident in EAMG mice with severe muscle weakness. However, the relationship between muscle weakness and bone loss in EAMG has not been studied before. Recent investigations on bone have shed light on association of bone health and immunological states. It is possible that muscle weakness in EAMG developed by anti-tAChR immune responses might accompany bone loss. We determined whether reduced muscle strength associates with decreased bone mineral density (BMD) in EAMG mice. EAMG was induced by two injections at 4-week interval of tAChR and adjuvants in two different age groups. The first tAChR injection was either at age 8 weeks or at 15 weeks. We measured BMD at three skeletal sites, including femur, tibia, and lumbar vertebrae, using dual energy X-ray absorptiometry. Among these bone areas, femur of EAMG mice in both age groups showed a significant decrease in BMD compared to control adjuvant-injected and to non-immunized mice. Reduction in BMD in induced EAMG at a later-age appears to parallel the severity of the disease. The results indicate that anti-tAChR autoimmune response alone can reduce bone density in EAMG mice. BMD reduction was also observed in adjuvant-injected mice in comparison to normal un-injected mice, suggesting that BMD decrease can occur even when muscle activity is normal. Decreased BMD observed in both tAChR-injected and adjuvant-injected mice groups were discussed in relation to innate immunity and bone-related immunology involving activated T cells and tumour necrosis factor-related cytokines that trigger osteoclastogenesis and bone loss.